The coalition government's record on tax - Roantree, Barra (The Institute for Fiscal Studies, 2015)
As part of its deficit reduction programme, the coalition government has made tax changes whose direct impact is to reduce borrowing by £16.4 billion in 2015---16: the net effect of £64.3 billion of tax rises and £48.0 billion of tax cuts. Despite these tax-raising reforms, government revenues as a share of national income are forecast to be no higher in 2015---16 than they were in 2009---10, since growth in individuals’ earnings and companies’ taxable profits has been unusually slow. • The biggest tax increases were implemented early in the parliament: a rise in the main rate of VAT from 17.5% to 20%, a sharp reduction in the amount that can be saved in tax-privileged pensions, and a 1 percentage point increase in employer, employee and self-employed rates of National Insurance contributions (NICs) that had already been pencilled in by the previous Labour government. • The government has also managed to find scope for three big tax cuts with a combined cost of £19.5 billion in 2015---16. Increasing the income tax personal allowance to £10,600 has cost £8.0 billion (net of reductions to the higher-rate threshold), reducing the main rate of corporation tax from 28% to 20% has cost £7.6 billion, and real-terms cuts to fuel duties have cost £3.9 billion. • For the most part, the reforms introduced by the coalition have involved changes to rates and thresholds with little attempt to address the fundamental structural deficiencies of the tax system. VAT has been increased but its base not broadened. Fuel duties have been cut but their increasing unsuitability for tackling congestion has not been addressed. Corporation tax has been cut but its base continues to distort investment and financing decisions. Income tax and NICs rates and thresholds have been changed but the two taxes have not been integrated. Business rates have been cut but made more unstable and continue to discourage property- intensive production. Council tax has been cut but allowed to get ever more out of date. Inheritance tax has been increased but its loopholes untouched. Capital gains tax has been increased but with no clear strategy for dealing with the tension between minimising disincentives to save and minimising avoidance opportunities. There have been some welcome structural reforms, but even there the job is incomplete. Stamp duty land tax no longer has big jumps in liabilities at price thresholds for housing, but still does have them for non-domestic properties, and the more fundamental problems with the tax remain. The use of the discredited retail prices index to adjust the system for inflation has been ended for direct taxes, but not for indirect taxes, and an increasing number of thresholds are not uprated at all. • The coalition has made some admirable improvements to the institutions of tax policy, enhancing transparency and allowing better scrutiny. But the way in which it has announced tax policy has not always been so admirable. While in some areas the government followed a clear plan, as with the corporate tax road map, other areas --- such as fuel duties and business rates --- have seen a stream of ad hoc, often temporary, announcements overtaking each other without a clear statement of principles or long-run intentions. • The next government will face two immediate challenges: what role (if any) tax changes should play in reducing the still-large budget deficit, and how to manage the devolution of tax-setting powers to different parts of the UK. There are also longer-term challenges. Incomes have become more concentrated in the hands of a small number of people, which may lead governments to want to tax them more heavily but also means that tax revenues are already perilously reliant on this group. And the international mobility of tax bases continues to grow. Long-standing weaknesses in the tax system also remain to be addressed, and the next government would do well to set out a strategy for doing so.
PUBLISHED
Keywords: Inclusive Society